Modified engineering plastic and preparation method thereof

By adding interfacial bonding strength enhancement units, crosslinking units, and thermal expansion coefficient adjustment units to polyphenylsulfone resin, and combining functional additives with metal affinity groups and resin compatibility groups, the thermal mismatch problem at the plastic-metal interface under thermal cycling was solved, improving the interfacial bonding strength and stability, and realizing the reliability of modified engineering plastics and aluminum alloys.

CN121374893APending Publication Date: 2026-01-23DONGGUAN WEIFENG NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511592791.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-03
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing modified engineering plastics preparation technologies have failed to effectively control the thermal mismatch problem at the plastic-metal interface under thermal cycling, resulting in a significant decrease in adhesion strength with the use environment and insufficient long-term stability of the interfacial bond, which limits the reliability of the bond between engineering plastics and aluminum alloys.

Method used

By adding interfacial bonding strength enhancing units, crosslinking units, and thermal expansion coefficient regulating units to polyphenylsulfone resin, and combining functional additives with metal affinity groups and resin compatibility groups, a directional modified engineering plastic is formed through twin-screw melt blending, spraying, and stretching treatment, ensuring interfacial bonding strength and stability.

Benefits of technology

It improves the bonding strength and service stability between modified engineering plastics and aluminum alloys, reduces thermal cycling stress, enhances interfacial adhesion and durability, and achieves consistency and long-term stability of interfacial construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121374893A_ABST
    Figure CN121374893A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of engineering plastics, and discloses a modified engineering plastic and a preparation method thereof.The preparation method comprises the steps that S1, polyphenyl sulfone resin and functional filler are sequentially added into double-screw melt blending equipment, mixing is conducted under preset conditions, and premixed master batches are obtained, the functional filler comprises an interface bonding strength enhancing unit, a crosslinking unit and a thermal expansion coefficient adjusting unit; and S2, spraying a dilute solution containing a functional auxiliary agent on the premixed master batch at a preset temperature, drying and curing the dilute solution on the surface of the premixed master batch through hot air, stretching in a stretching machine head, and annealing to obtain the functional aggregate with interfacial activity and a surface oriented structure. According to the modified engineering plastic and the preparation method thereof, the bonding strength, the use stability and the environment durability and reliability of the molten modified engineering plastic and an aluminum alloy material are improved by reducing the thermal cycling stress and the mechanical interlocking performance and keeping the consistency of the modified engineering plastic.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of engineering plastics, in particular to a modified engineering plastic and a preparation method thereof. BACKGROUND

[0002] With the rapid development of high-performance structural materials in the fields of aerospace, rail transportation, new energy vehicles and electronic packaging, the demand for the composite use of engineering plastics and metal substrates is increasing. Especially under the background of the increasing demand for lightweight and environmental resistance, high-performance engineering plastics such as polyphenyl sulfone (PPSU) and polyether ether ketone (PEEK) are widely used in scenarios that require fusion bonding with aluminum alloy substrates due to their excellent high-temperature resistance, chemical corrosion resistance and mechanical properties. For example, in the power battery shell, lightweight structure connecting piece, electronic device insulation layer and heat-resistant support, the firm combination of engineering plastics and aluminum alloy not only affects the overall strength of the product, but also directly relates to the stability and durability during service. How to improve the reliability of the plastic and aluminum alloy combination interface through material design has become the focus of the industry.

[0003] The existing preparation technology of modified engineering plastics mainly improves the interface performance by introducing fillers or additives into the resin, such as adding inorganic fillers to improve rigidity, or introducing reactive monomers to enhance interface bonding. However, the modification measures from a single perspective often rely only on inorganic fillers to improve mechanical properties, but fail to effectively control the thermal mismatch problem of the plastic and metal interface under cold and hot cycles, resulting in a significant decrease in adhesion strength with the use environment. This defect directly causes the long-term stability of the interface combination to be insufficient, limiting the reliability of the engineering plastics and aluminum alloy after injection molding. SUMMARY

[0004] In view of the deficiencies of the prior art, the present application provides a modified engineering plastic and a preparation method thereof, which solves the problems raised in the background art.

[0005] To achieve the above purpose, the technical scheme is as follows: A modified engineering plastic and a preparation method thereof are designed, comprising: S1, polyphenyl sulfone resin and functional filler are sequentially added to a twin-screw melt blending device, and mixing is carried out under preset conditions to obtain a premixed master batch, wherein the functional filler includes an interface bonding strength enhancing unit, a crosslinking unit and a thermal expansion coefficient adjusting unit; S2, a dilute solution containing a functional additive is sprayed on the premixed master batch at a preset temperature, and is dried and solidified on the surface of the premixed master batch by hot air, then stretched in a stretching machine head, and after annealing treatment, a functional granule with interface activity and surface directional structure is obtained, wherein the functional additive includes a metal affinity group and a resin compatible group; S3, drying the functional granules to obtain the to-be-tested plastic, detecting a performance parameter of the to-be-tested plastic after melting at a preset detection temperature, judging whether the performance parameter is located in a qualified interval, if not, determining that the product is unqualified, and adjusting a process parameter according to the detected performance parameter, if yes, determining that the modified engineering plastic is qualified, wherein the performance parameter includes a melt viscosity and an interfacial activity coverage rate.

[0006] Optionally, S1 specifically includes: S11, after drying and dehumidifying the polyphenylsulfone resin, adding the polyphenylsulfone resin into the twin-screw melt blending device through the main feeding port, so that the polyphenylsulfone resin is gradually heated, softened and forms a continuous stable melt band; S12, after obtaining the stable melt band, making the stable melt band enter the first shear region and the second shear region in sequence, and adding the thermal expansion coefficient adjusting unit, the crosslinking unit and the interfacial bonding strength enhancing unit in sequence, so that the functional filler is uniformly distributed in the stable melt band through dispersion processing, and a functional melt band is obtained; S13, sequentially arranging two-stage vacuum exhaust ports on the twin-screw melt blending device, and using staged air extraction to make the functional melt band expand into a film and perform trace inert gas stripping treatment, so as to expand the melt surface area of the functional melt band and promote the migration of volatile substances, and a premix melt is obtained; S14, filtering the premix melt, and then extruding and pelletizing to obtain a premix master batch.

[0007] Optionally, S12 specifically includes: S121, after obtaining the stable melt band, making the stable melt band enter the first shear region with a first shear condition in the twin-screw melt blending device, and adding the thermal expansion coefficient adjusting unit for blending, so as to form in-plane orientation along the flow direction of the stable melt band, and obtain a stable melt band with a primary dispersed phase; S122, making the stable melt band with the primary dispersed phase transition from the first shear region to the second shear region with a second shear condition, and adding the crosslinking unit through the side feeding port for blending, so as to obtain an intermediate melt band; S123, adding the interfacial bonding strength enhancing unit in the intermediate melt band, and performing blending through staged blending, so as to obtain the functional melt band, wherein the staged blending includes a first stage with the second shear condition, a second stage with the first shear condition and a third stage with the second shear condition.

[0008] Optionally, the first shear condition includes a shear rate of 200-800 s -1 , a shear stress of 10 5 -10 6 Pa, and the second shear condition includes a shear rate of 10-100 s -1 , a shear stress of 10 4 -10 5 Pa.

[0009] Optionally, S2 specifically comprises: S21, placing the premix master batch in a tumbling drum at a preset temperature, spraying a dilute solution containing a functional additive on the premix master batch, wherein the functional additive contains both a metal affinity group and a resin compatible group, and performing staged hot air drying on the premix master batch sprayed with the functional additive, so that the functional additive forms a dense continuous layer on the surface of the premix master batch, and an intermediate product of the premix master batch with interfacial activity is obtained; S22, feeding the intermediate product of the premix master batch into a stretching head for stretching, so that the surface layer of the intermediate product of the premix master batch generates shear flow and thin layer spreading, the functional additive is further uniformly spread along the surface of the intermediate product of the premix master batch, and the near-surface structure is guided to in-plane orientation, and a functionalized particle with a surface oriented structure is obtained; S23, performing isothermal annealing treatment on the functionalized particle, so that the surface oriented structure and the interfacial activity are double-locked, and a functional granular material with interfacial activity and surface oriented structure is obtained.

[0010] Optionally, the metal affinity group includes at least one of phosphonic acid group, phosphoric acid group, carboxyl group, catechol group or silanol group, and the resin compatible group includes at least one of aromatic ring, ketone group, sulfone group or ether group.

[0011] Optionally, S3 specifically comprises: S31, drying the functional granular material in a vacuum environment to remove adsorbed moisture and residual volatile matter, and after drying, sealing, transporting and numbering the functional granular material in an inert atmosphere, and obtaining a plastic to be detected; S32, preparing a sample by melting the plastic to be detected at a preset detection temperature, and simultaneously performing parameter testing of melt viscosity and interfacial activity coverage, obtaining parameters of melt viscosity and interfacial activity coverage, and collecting performance parameters; S33, comparing the parameters of melt viscosity and interfacial activity coverage in the performance parameters with a preset qualified interval, if any parameter is not in the qualified interval, determining that the batch is unqualified, optimizing process parameters according to the parameters of melt viscosity and interfacial activity coverage, obtaining optimized parameters, and delivering the optimized parameters to a preparation control system to dynamically adjust process parameters in a subsequent preparation process, wherein the process parameters include drying parameters and shear parameters; S34, when the parameters of melt viscosity and interfacial activity coverage in the performance parameters are in the qualified interval, determining that the batch is a qualified modified engineering plastic.

[0012] Optionally, the performance parameter testing includes obtaining a melt viscosity curve by using a rheological method, and quantitatively characterizing the interfacial activity coverage by identifying the functional additive.

[0013] The application provides a modified engineering plastic and a preparation method thereof.

[0014] The application provides a modified engineering plastic and a preparation method thereof. The modified engineering plastic preparation method provides metal affinity chemical sites through the interface bonding strength enhancing unit at the moment of melt bonding to improve initial adhesion, and the cross-linking unit solidifies in situ in the vicinity of the interface to form a thin layer of reticular phase to improve the proportion of cohesive fracture and durability, and the thermal expansion coefficient adjusting unit is reasonably dispersed to reduce cold and hot cycle stress, the metal affinity group and the resin compatible group of the functional additive are used to direct the surface layer, the interface bonding strength enhancing unit is enriched in the near surface layer, better wetting and mechanical interlocking are obtained during melt flow, initial adhesion and long-term stability are considered, closed-loop control is formed by taking melt viscosity and interface activity coverage as indexes, the consistency of the modified engineering plastic interface structure is ensured, the preparation is performed by reducing cold and hot cycle stress, mechanical interlocking performance and maintaining the consistency of the modified engineering plastic, and then the bonding strength, use stability and environmental durability and reliability of the modified engineering plastic after melting and the aluminum alloy material are improved. BRIEF DESCRIPTION OF DRAWINGS

[0015] Figure 1 Figure 1 is one of flowcharts of the modified engineering plastic preparation method in the application. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the application will be clearly and completely described in combination with the accompanying drawings in the embodiments of the application, and all other embodiments obtained by those skilled in the art without creative labor on the basis of the embodiments in the application belong to the protection scope of the application.

[0017] Please refer to Figure 1 The application provides a technical solution: a modified engineering plastic preparation method, which comprises the following steps. S1, polyphenyl sulfone resin and functional fillers are sequentially added into a double-screw melt blending device, and mixing is performed under preset conditions to obtain a premixed master batch, wherein the functional fillers comprise an interface bonding strength enhancing unit, a cross-linking unit and a thermal expansion coefficient adjusting unit; Specifically, the interface bonding strength enhancement unit is a group that can react with the aluminum alloy oxide film or strongly adsorb, at least one of the phosphonic acid group, the phosphoric acid group or the ortho-diphenol group, which can be a small molecule, a grafted oligomer or a surface modifier, the cross-linking unit is a cross-linking precursor that remains latent within the processing temperature range and only undergoes chemical cross-linking when the subsequent bonding or forming is performed, and specifically at least one of a benzoxazine prepolymer or a latent epoxy material, the latent epoxy material is obtained by mixing a bisphenol A type epoxy resin (latent epoxy precursor) with a latent curing agent (at least one of an imidazole salt or an amine salt), and the coefficient of thermal expansion adjustment unit is specifically a sheet-shaped inorganic filler (such as at least one of sheet-shaped aluminum oxide, hexagonal boron nitride or mica sheet), which is used to reduce the coefficient of thermal expansion of the material perpendicular to the interface. S1 specifically includes: S11, after drying and dehumidifying the polyphenyl sulfone resin, the polyphenyl sulfone resin is gradually heated, softened and formed into a continuous stable melt zone through the main feeding port of the twin-screw melt blending device. The polyphenyl sulfone resin is extremely easy to absorb moisture, and moisture at high temperature can cause the resin molecular chain to break and form bubbles. Therefore, the resin needs to be dried under vacuum or hot air conditions. After drying, the resin is added to the twin-screw melt blending device through the main feeding port, and gradually softens and melts under the action of temperature gradient and shear. A continuous stable melt zone is formed through the conveying elements (i.e. screw) of the twin-screw melt blending device, forming a stable flow matrix to provide a uniform carrying environment for subsequent filler addition. By drying and dehumidifying the polyphenyl sulfone resin, adsorbed moisture and volatile small molecules are effectively removed, avoiding defects such as bubbles, silver streaks or molecular chain degradation in the subsequent melt processing. Finally, a continuous melt zone with stable torque and pressure is formed in the twin-screw melt blending device (which is a known technology), ensuring that the material can stably accept functional fillers.

[0018] S12, after obtaining the stable melt zone, the stable melt zone is sequentially introduced into the first shear zone and the second shear zone, and the coefficient of thermal expansion adjustment unit, the cross-linking unit and the interface bonding strength enhancement unit are sequentially added, so that the functional fillers are uniformly distributed in the stable melt zone through dispersion processing, and a functional melt zone is obtained. The preset first shear condition includes a shear rate of 200-800 s -1 , and a shear stress of 10 5 -10 6 Pa, and the second shear condition includes a shear rate of 10-100 s -1 , and a shear stress of 10 4 -10 5 Pa.

[0019] S12 specifically includes: S121, after obtaining the stable melt band, the stable melt band enters a first shear region of the twin-screw melt blending device under a first shear condition, a thermal expansion coefficient adjusting unit is added for blending, in-plane orientation is formed along the flow direction of the stable melt band, and a stable melt band with a primary dispersed phase is obtained; Under the first shear condition (relatively high shear), relatively high shear stress and frequent interface renewal are caused, the flaky inorganic filler is quickly wetted by the resin in the stable melt band and is mechanically peeled into thinner layers, at the same time, the shear flow and the local extension flow drive the flaky filler to lie horizontally in the flow plane (i.e. in-plane orientation), the in-plane oriented flaky skeleton limits the thermal expansion in the vertical direction (equivalent stiffening), so as to relieve the thermal mismatch stress between the engineering plastic and the aluminum alloy in the subsequent thermal cycle, the thermal expansion coefficient adjusting unit (flaky inorganic filler) is transformed from an agglomerate into a state of thinning, refinement and uniform dispersion, and forms in-plane orientation in the flow plane; the thermal expansion coefficient of the stable melt band is significantly reduced, the shear bearing capacity of the interface layer and the cold and hot cycle stability are improved, and a stable, low-stress base melt band is provided for the subsequent addition of other functional units; S122, the stable melt band with a primary dispersed phase is transferred from the first shear region to a second shear region under a second shear condition, a cross-linking unit is added at the side feed port for blending, and a medium melt band is obtained, the second shear condition (low shear) mainly controls the shear rate and temperature rise by mixing transportation and distribution, and reduces local stress peaks; the cross-linking precursor (such as benzoxazine prepolymer, latent epoxy precursor and its latent curing agent) is coated and dispersed by the resin matrix in the stable melt band, but will not trigger a chemical reaction at this temperature / stress, thus the cross-linking unit exists in a non-reacted but reactive form, and generates a cross-linked phase to enhance cohesion when the trigger condition (such as higher temperature or specific time) is reached later, the cross-linking unit is fully wetted by the resin and uniformly distributed macroscopically in a low shear environment, while remaining in a latent state, without premature cross-linking or abnormal viscosity rise, thereby obtaining a medium melt band (note: the "medium melt band" here refers to the intermediate state of the same continuous melt band after further blending of the cross-linking unit based on S121), which creates conditions for in-situ cross-linking and interface cohesion enhancement in the subsequent molding / fitting stage; S123, adding interface bonding strength enhancing units in the intermediate melt band, blending by stage blending, to obtain a functional melt band, wherein the stage blending includes a first stage using a second shear condition, a second stage using a first shear condition, and a third stage using a second shear condition, the first stage reduces the interfacial surface tension and diffusion barrier, allowing the group-containing adjuvant to penetrate and spread in the stable melt, the second stage provides a transient higher energy input, depolymerizes residual small agglomerates and refreshes the resin matrix and adjuvant contact interface, improves effective coverage, completes re-homogenization and rheological stability, avoids continuous relative high shear leading to chemical group deactivation or secondary agglomeration, and the group (such as at least one of phosphonic acid group, phosphoric acid group or ortho-diphenol group) can form coordination bond or condensation bond (for example, Al–O–P, or multi-point hydrogen bond / coordination) when subsequently contacted with aluminum alloy oxide film, thereby realizing chemical anchoring at the interface; and the in-plane oriented sheet-shaped filler formed in S121 provides micro-mechanical interlocking and thermal expansion matching, both of which synergistically improve adhesion strength and durability; In the twin screw mechanism, short high shear is not maintained throughout the entire screw, but a small section of high shear element combination is embedded in the conveying / distribution section of the low shear zone, a small amount of kneading block is inserted, the angle is large (45° or 60°), a transient high shear environment is formed, a reverse element or a flow resistance ring is used to create a local back pressure, causing a short-term high stress zone, which is well known to those skilled in the art; Under the first shear condition (shear rate 200-800 s -1 , shear stress 10 5 -10 6 Pa), the sheet-shaped inorganic filler is broken up by relatively strong shear force, the stable melt band wets the surface of the sheet-shaped inorganic filler, the sheet-shaped inorganic filler is arranged parallel to the flow direction (i.e., in-plane orientation), and the thermal expansion mismatch of the interface is reduced; then the stable melt band enters the second shear condition (shear rate 10-100 s -1 , shear stress 10 4 -10 5 Pa), the crosslinking unit is dispersed in a low shear environment and will not react prematurely due to local high temperature or stress; finally, the interface enhancing unit is dispersed under the stage treatment of relatively low shear-short-term relatively high shear-relatively low shear, first penetrates mildly, then refreshes the interface and breaks up small agglomerates under short-term relatively high shear force, and then stabilizes mildly, finally ensuring uniform distribution of the adjuvant without deactivation.

[0020] S13, two-stage vacuum exhaust ports are arranged in sequence on the twin-screw melt blending device, and staged evacuation is adopted to make the functional melt zone expand into a film and perform trace stripping treatment of inert gas, expand the melt surface area of the functional melt zone, and promote the migration of volatile substances, to obtain a premix melt, the two-stage vacuum exhaust refers to sequentially arranging two exhaust ports in the twin-screw barrel, the first-stage exhaust port preferentially exhausts volatile components (such as water, residual solvent) by relatively mild vacuum evacuation, and the second-stage exhaust port further evacuates small molecules that are difficult to volatilize under higher vacuum, to prevent air from being sucked back and the melt from overflowing, the upstream and downstream of the exhaust port are sealed by the screw geometry (such as reverse conveying elements, kneading elements) to form a melt seal, the melt film expansion refers to spreading the melt of the functional melt zone into a thin layer or a wide band in the exhaust zone to significantly increase the contact area of the melt-vacuum, shorten the diffusion path of small molecules from the interior to the surface of the melt of the functional melt zone, and thus accelerate the devolatilization, the trace stripping of inert gas refers to introducing a small amount of inert gas (such as nitrogen / argon) into the center of the melt of the functional melt zone to form a micro-bubble channel, reduce the partial pressure of volatile substances in the melt of the functional melt zone, and provide gas-liquid mass transfer stripping effect, to promote the volatile substances to migrate to the free surface with the bubbles and then be taken away by the vacuum, and cooperate with the cold trap and the trap to avoid the return of condensate and pollution of the vacuum pump, to realize efficient devolatilization, and obtain a premix melt; S14, after filtering the premix melt, extruding and pelletizing to obtain a premix master batch, the filtering physically intercepts the melt by a screen / filter plate (also known as a screen group and a support plate) to remove large-particle impurities and gels, and keep the extrusion channel unobstructed and the die head pressure stable; then the premix melt is formed into a strip or a granular precursor by the die head at a stable flow rate, is quickly and uniformly cut into granules in the underwater pelletizing or cooling water tank + pull rod pelletizing process, and is dehydrated / dried to obtain a master batch with low water content and complete surface, due to devolatilization, the premix melt no longer releases gas during extrusion and cooling, and the internal and surface defects of the premix master batch are significantly reduced, further removing gels and hard particles (gels, which are insoluble micro-agglomerates formed due to local overheating / early crosslinking) on the basis of the premix melt, stabilizing the die head back pressure and the extrusion flow field, and avoiding scratches on the die port or the formation of defective particles during granulation; after controlled extrusion and pelletization, a premix master batch with uniform particle size, apparent cleanliness, and low residual volatile substances is obtained, which is beneficial to the subsequent spraying of functional additives and the processing stability and batch consistency of the stretching / annealing process, and improves the reliability of the final material appearance and interface bonding.

[0021] S2, spraying a dilute solution containing functional additives on the premix master batch at a predetermined temperature, and drying and solidifying on the surface of the premix master batch by hot air, then stretching in a stretching die head, and obtaining a functional granule with interfacial activity and surface directional structure after annealing treatment, wherein the functional additives include metal affinity groups and resin compatible groups; The metal affinity group comprises at least one of a phosphonic acid group, a phosphoric acid group, a carboxyl group, a catechol group or a silanol group, and the resin compatible group comprises at least one of an aromatic ring, a ketone group, a sulfone group or an ether group.

[0022] S2 specifically comprises: S21, placing the premix master batch in a tumbling drum at a preset temperature, spraying a dilute solution containing a functional additive, wherein the functional additive contains both a metal affinity group and a resin compatible group, performing staged hot air drying on the premix master batch sprayed with the functional additive, the functional additive forming a dense continuous layer on the surface of the premix master batch, obtaining an intermediate product of the premix master batch with interfacial activity, the dilute solution refers to a solution with low solid content, which can quickly wet each functional granular particle and spontaneously spread into a film in a tumbling / fluidized state; the staged hot air drying refers to a drying curve of fast first and slow later, or low first, medium later and stable finally, the use of volatilization gradient promotes the densification of the film layer without cracking, the resin compatible group (aromatic ring, ketone group, sulfone group, ether group) and the polyphenylsulfone (PPSU) main chain occur π-π stacking, dipole-dipole attraction and physical entanglement, anchoring the film layer to the skin; the metal affinity group (phosphonic acid / phosphoric acid / carboxyl / catechol / silanol) is preferentially exposed on the outside of the film layer, providing a chemical site for subsequent metal bonding, the premix master batch is sprayed with a dilute solution at a preset temperature and subjected to staged hot air drying, so that the functional additive constructs a dense continuous layer on the surface of the granule, the outside of the layer is rich in metal affinity groups (for subsequent bonding with aluminum alloy oxide film Al-O X reacts, and is specifically used after melting during aluminum alloy injection molding), the inside is entangled / compatible with the polyphenylsulfone skin through the resin compatible group, so that the film layer is not easy to migrate and lose, is evenly covered and has interfacial activity, obtaining an intermediate product of the premix master batch with interfacial activity; S22, sending the premix master batch intermediate product into the stretching head for stretching, causing the surface layer of the premix master batch intermediate product to generate shear flow and thin layer spreading, causing the functional additives to further uniformly spread along the surface of the premix master batch intermediate product and inducing the near-surface layer structure to in-plane orientation, obtaining a surface-oriented functionalized particle, the controlled stretching / shear flow field provided by the stretching head causes the surface layer film to undergo viscoelastic flow, on the one hand, the film spreads under the driving of surface tension, eliminating the local unevenness caused by spraying; on the other hand, the shear along the flow direction promotes the orientation of the chain segments and the laying of the flaky filler (i.e. in-plane orientation), reducing the free volume change in the vertical direction, and thus reducing the normal thermal expansion. Since the resin matrix in the premix master batch intermediate product and the film layer have been entangled through compatible groups, the film layer will not separate after flowing but will be rearranged into a more stable uniform covering. After sending the premix master batch intermediate product into the stretching head, the surface layer generates shear flow and thin layer spreading, and the functional additives further uniformly spread along the surface of the particle, while inducing the in-plane orientation (parallel arrangement along the surface plane direction) of the near-surface layer chain segments and the flaky filler that may exist. As a result, the film layer is more uniform in thickness and local defects are smoothed out, and the surface energy is more controllable; the in-plane orientation reduces the near-surface layer normal thermal expansion coefficient and improves the surface layer shear modulus, creating conditions for wetting and spreading and micro-mechanical interlocking during subsequent melt bonding; S23, isothermal annealing treatment is performed on the functionalized particles to complete the double locking of the surface-oriented structure and the interfacial activity, obtaining functional granules with interfacial activity and surface-oriented structure. Isothermal annealing refers to keeping at a constant temperature for a certain period of time to allow the polymer surface layer molecular chain segments to relax, stress to be released, and limited interdiffusion and physical aging (densification) to occur. During this process, the interaction between the resin compatible groups (aromatic ring / keto group / sulfone group / ether group) and PPSU is further rearranged to increase stability, thereby locking the film layer. At the same time, the annealing temperature / time is controlled to prevent the metal affinity groups of the functional additives from being buried or chemically deactivated, maintaining their reaction / coordination ability with the aluminum alloy oxide film, achieving the dual goals of orientation locking and activity preservation. After isothermal annealing of the functionalized particles, the orientation formed by stretching is long-term stable, and chain segment interdiffusion and densification occur in the film layer, making the anchoring of the compatible groups and the PPSU skin more firm. Without damaging the functional molecules, the outside metal affinity groups remain exposed and active, so that the final functional granules have both surface-oriented structure and sustained interfacial activity, providing a reliable premise for chemical anchoring (such as forming Al–O–P bonds or multiple-point hydrogen bonds / coordination) and stable wetting during melt bonding.

[0023] S3, drying the functional granules to obtain the plastic to be detected, detecting the performance parameters of the plastic to be detected after melting at a preset detection temperature, judging whether the performance parameters are within a qualified interval, if not, determining that it is unqualified, and adjusting the process parameters according to the detected performance parameters, if yes, determining that it is a qualified modified engineering plastic, wherein the performance parameters include melt viscosity and interfacial activity coverage rate; The granules are pretreated and detected under standardized conditions, three types of index representing melt flow, surface morphology and interfacial functional site are quantified and compared with the qualified interval; when any index deviates, the process settings such as drying, dispersion and shearing are adjusted according to the deviation direction, and then fed back to the preparation link to realize parameter self-adaptation and continuous correction S3 specifically includes: S31, drying the functional granules in a vacuum environment to remove adsorbed moisture and residual volatile matter, sealing and transferring in an inert atmosphere after drying, and numbering and archiving to obtain the plastic to be detected, the polyphenyl sulfone granules have a certain hygroscopicity, and moisture and low molecular residue can cause chain degradation or form micropores / bubbles at high temperature, thereby affecting viscosity and surface morphology, the granules are placed in a vacuum drying device (vacuum reduces water / small molecule partial pressure, promotes removal), and after drying, they are sealed in an inert atmosphere (such as nitrogen) to avoid re-hydration and oxidation; then numbering and archiving (recording batch number and drying completion time) are performed to form the plastic to be detected, adsorbed moisture and residual volatile matter are removed by vacuum drying to avoid bubbles, silver streaks and viscosity drift during subsequent melting tests; inert atmosphere sealing, transferring and numbering and archiving ensure that the sample is not re-hydrated or contaminated during the inspection process, and realize traceable batch management, thereby improving the reliability and comparability of the detection data from the source.

[0024] S32, melting the plastic to be detected at a preset detection temperature to prepare a sample, and simultaneously performing parameter tests of melt viscosity and interfacial activity coverage rate to obtain the parameters of melt viscosity and interfacial activity coverage rate, and collecting the performance parameters; The performance parameter test includes obtaining a melt viscosity curve by rheological method, and quantitatively characterizing the interfacial activity coverage rate by recognizing the functional additive; Specifically, the melt viscosity (rheological method) detection is performed on a rotational rheometer (parallel plate or cone plate) or a capillary rheometer at a preset temperature, i.e., 300℃ (±5℃), with a shear rate of 100 s -1Scanning, recording viscosity-shear rate curve; release viscosity can be read at specified shear rate point, interfacial activity coverage detection adopts identifiable detection on functional additives, such as using X-ray photoelectron spectroscopy (XPS) to detect surface characteristic elements / chemical bonds (such as P2p corresponding phosphonic acid or O1s component change), or after fluorescence labeling of the additive, using confocal microscopic imaging and calculating coverage percentage according to threshold value, establishing intensity and coverage corresponding relationship through internal standard / calibration sheet to obtain quantitative value of interfacial activity coverage, detection method is a known technology, which will not be described in detail here; Three parameters obtained synchronously at preset detection temperature at one time, melt viscosity curve reflects the fluidity and structural stability of melt at different shear rates, interfacial activity coverage quantifies the effective coverage degree of surface functional additives (containing metal affinity group) on the surface of particles or thin layer, and is collected as performance parameters to evaluate whether the interface construction meets the standard.

[0025] S33, compare the melt viscosity and interfacial activity coverage parameters in the performance parameters with the preset qualified interval respectively, if any parameter is not in the qualified interval, determine that the batch is unqualified, optimize the process parameters according to the melt viscosity and interfacial activity coverage parameters, obtain the optimized parameters, and deliver the optimized parameters to the preparation control system to dynamically adjust the process parameters in the subsequent preparation process, wherein the process parameters include drying parameters and shear parameters; The qualified interval of melt viscosity is 1500-4000 Pas (280-320℃, shear rate 100 s -1 measured); The interfacial activity coverage is the effective surface coverage percentage, and the qualified interval is ≥80%; The drying parameters are specifically that the drying time in S31 is 8-16 h, and the vacuum degree is 0.09 MPa; The shear parameters are specifically the first shear condition and the second shear condition; If the melt viscosity is <1500 Pa·s and the interfacial activity coverage is >80%, it indicates that the functional granules are not dried enough (residual water / volatiles play a dilution and degradation induction role), or high-strength shear leads to molecular chain rupture, chain degradation or too much residual water / volatiles, then the drying time is extended by 2-4 h, the vacuum degree is increased by 0.01 MPa, and the shear rate of the first shear condition in S121 is reduced by 10-20% (about 50 150 s -1 ).

[0026] If the melt viscosity is >4000 Pa·s and the interfacial activity coverage is >80%, it is related to the premature reaction (triggered by shear / temperature rise) or local retention of latent crosslinking units. That is, if the crosslinking units react prematurely or are locally retained, the shear rate of the first shear condition in S121 is reduced by 10–20% (approximately). 50~ 150s -1 And shorten a set of components, that is, reduce the helical kneading block on the corresponding helical rod, specifically by reducing the helical kneading block by 10% proportionally, maintaining the second shearing condition in S122, and increasing the dwell time by 10–20%. If the melt viscosity is >4000 Pa·s and the interfacial activity coverage is <80%, the shear rate under the first shear condition in S121 is reduced by 10–20% (approximately). 50~ 150s -1 And shorten a set of elements. In S123, a second stage is added after the third stage to form a fourth stage, and the shear rate of the second stage is increased by 50-100 s. -1 The drying time is extended by 1–2 hours, and the vacuum degree is increased by 0.005–0.01 MPa; If the melt viscosity is <1500 Pa·s and the interfacial activity coverage is <80%, the drying time should be extended by 2–4 hours, the vacuum degree increased by 0.01 MPa, and the shear rate under the first shear condition in S121 reduced by 10–20% (approximately). 50~ 150s -1 Furthermore, the shear rate increases by 50–100 s in the second stage. -1 The spiral kneading blocks in the third stage are increased by 10%–15%.

[0027] S34. When the melt viscosity and interfacial activity coverage parameters are both within the qualified range, the batch is determined to be a qualified modified engineering plastic.

[0028] A modified engineering plastic, characterized in that it is prepared by the modified engineering plastic preparation method described above, wherein the modified engineering plastic comprises a polyphenylsulfone matrix, a functional additive layer is attached to the surface of the polyphenylsulfone matrix, the functional additive layer comprises metal affinity groups and resin compatible groups, and forms an oriented structure on the surface, and a composite structure is uniformly dispersed in the polyphenylsulfone matrix, the composite structure comprising a thermal expansion coefficient adjustment unit, a crosslinking unit, and an interfacial bonding strength enhancement unit.

[0029] While embodiments of the application have been shown and described, it is to be understood that the embodiments described are merely exemplary of the principles and application of the present application. Numerous modifications and adaptions can be effected without departing from the spirit and scope of the present application, which is not limited to the exact construction and arrangement described. It is intended, therefore, to cover all modifications and adaptions that fall within the scope of the claims and their equivalents.

Claims

1. A method for producing a modified engineering plastic, characterized by, The application relates to a method for preparing a modified engineering plastic, and belongs to the field of polymer modification. The method comprises the following steps: S1, adding polyphenylsulfone resin and functional fillers into a double-screw melt blending device in sequence, and mixing under preset conditions to obtain premix masterbatch, wherein the functional fillers comprise interface bonding strength enhancing units, crosslinking units and thermal expansion coefficient adjusting units; S2, spraying a dilute solution containing functional additives on the premix masterbatch at a preset temperature, and performing hot air drying and solidification on the surface of the premix masterbatch, then performing stretching in a stretching machine head, and obtaining functional granules with interface activity and surface directional structure after annealing treatment, wherein the functional additives comprise metal affinity groups and resin compatible groups; 2. The method for preparing modified engineering plastics according to claim 1, characterized in that, S3, drying the functional granules to obtain a to-be-detected plastic, detecting the performance parameters of the to-be-detected plastic after melting at a preset detection temperature, judging whether the performance parameters are located in a qualified interval, if not, judging as unqualified products, and adjusting process parameters according to the detected performance parameters, if yes, judging as qualified modified engineering plastics, wherein the performance parameters comprise melt viscosity and interface activity coverage. S1 specifically comprises the following steps: S11, after drying and dehumidifying the polyphenylsulfone resin, the polyphenylsulfone resin is added into the double-screw melt blending device through a main feeding port, so that the polyphenylsulfone resin is gradually heated, softened and forms a continuous and stable melt band; S12, after obtaining the stable melt band, the stable melt band is sequentially introduced into a first shear region and a second shear region, and the thermal expansion coefficient adjusting units, the crosslinking units and the interface bonding strength enhancing units are sequentially added, so that the functional fillers are uniformly distributed in the stable melt band through dispersion processing, and a functional melt band is obtained; S13, two-stage vacuum exhaust ports are arranged on the double-screw melt blending device in sequence, and staged air exhaust is adopted to make the functional melt band expand into a film and perform trace inert gas stripping treatment, so that the melt surface area of the functional melt band is expanded and the migration of volatile matters is promoted, and a premix melt is obtained; 3. The method of claim 2, wherein the modifying step is performed by adding a modifier to the mixture of the engineering plastic and the solvent. S14, after filtering the premix melt, the premix melt is extruded and cut into particles to obtain the premix masterbatch. S12 specifically comprises the following steps: S121, after obtaining the stable melt band, the stable melt band is introduced into the first shear region with a first shear condition in the double-screw melt blending device, the thermal expansion coefficient adjusting units are added for blending, in-plane orientation is formed along the flow direction of the stable melt band, and a stable melt band with a primary dispersed phase is obtained; S122, the stable melt band with the primary dispersed phase is transferred from the first shear region to the second shear region with a second shear condition, the crosslinking units are added for blending through a side feeding port, and an intermediate melt band is obtained; 4. The method of claim 3, wherein the modifying step is performed by adding a modifier to the mixture of the engineering plastic and the solvent. said first shear condition comprises a shear rate of 200 - 800 s -1 -1 and a shear stress of 10 5 - 10 6 Pa, and said second shear condition comprises a shear rate of 10 - 100 s -1 -1 and a shear stress of 10 4 - 10 5 Pa.

5. The method for preparing modified engineering plastics according to claim 1, characterized in that, S123, the interface bonding strength enhancing units are added in the intermediate melt band, and blending is performed through staged blending, and the functional melt band is obtained, wherein the staged blending comprises a first stage with the second shear condition, a second stage with the first shear condition and a third stage with the second shear condition. S2 specifically comprises the following steps: S21, the premix masterbatch is placed in a turnover drum at a preset temperature, and a dilute solution containing functional additives is sprayed, wherein the functional additives simultaneously comprise metal affinity groups and resin compatible groups, the premix masterbatch sprayed with the functional additives is subjected to staged hot air drying, the functional additives form a dense and continuous layer on the surface of the premix masterbatch, and a premix masterbatch intermediate product with interface activity is obtained; S22, the premix master batch intermediate product is sent to a stretching machine head for stretching, so that the surface layer of the premix master batch intermediate product generates shear flow and thin layer spreading, the functional additives are further uniformly spread along the surface of the premix master batch intermediate product and guided to generate in-plane orientation of the near-surface layer structure, and the surface layer oriented functionalized particles are obtained; S23, the functionalized particles are subjected to isothermal annealing treatment, the double locking of the surface layer oriented structure and the interface activity is completed, and the functional granules with interface activity and surface layer oriented structure are obtained.

6. The method of claim 5, wherein the modifying step is performed by adding a modifier to the mixture of the engineering plastic and the solvent. The metal affinity group includes at least one of phosphonic acid group, phosphoric acid group, carboxyl group, catechol group or silanol group, and the resin compatible group includes at least one of aromatic ring, ketone group, sulfone group or ether group.

7. The method for preparing modified engineering plastics according to claim 1, characterized in that, S3 specifically includes: S31, the functional granules are placed in a vacuum environment for drying to remove adsorbed moisture and residual volatile substances, and after drying, the functional granules are sealed and transported in an inert atmosphere and numbered for archiving to obtain the plastic to be detected; S32, the plastic to be detected is melted for sample preparation at a preset detection temperature, and the parameters of melt viscosity and interface activity coverage are tested synchronously to obtain the parameters of melt viscosity and interface activity coverage, and the performance parameters are collected; S33, the parameters of melt viscosity and interface activity coverage in the performance parameters are compared with the preset qualified interval respectively, if any parameter is not in the qualified interval, it is determined that the batch is unqualified, the process parameters are optimized according to the parameters of melt viscosity and interface activity coverage, the optimized parameters are obtained, the optimized parameters are transported to the preparation control system, and the process parameters in the subsequent preparation process are dynamically adjusted, wherein the process parameters include drying parameters and shear parameters; S34, when the parameters of melt viscosity and interface activity coverage in the performance parameters are in the qualified interval, it is determined that the batch of modified engineering plastics is qualified.

8. The method of claim 7, wherein the modifying step is performed by adding a modifier to the mixture of the engineering plastic and the solvent. The performance parameter test includes obtaining the melt viscosity curve by using rheological method, and quantitatively characterizing the interface activity coverage by recognizing the functional additives.

9. A modified engineering plastic characterized by: The modified engineering plastics are prepared by the method of any one of claims 1-8, the modified engineering plastics include a polyphenyl sulfone matrix, a functional additive layer is attached to the surface of the polyphenyl sulfone matrix, the functional additive layer includes a metal affinity group and a resin compatible group, and a directional orientation structure is formed on the surface layer, the polyphenyl sulfone matrix uniformly disperses a composite structure, and the composite structure includes a thermal expansion coefficient adjusting unit, a crosslinking unit and an interface bonding strength enhancing unit.